BURDEN OF PROOF OF CUSTOMS VALUATION DISPUTES IN INDONESIAN TAX COURT - Ardiansyah; Atma Suganda (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
In applying the burden of proof of customs valuation disputes in the Indonesian tax court, some judges place the burden of proof to the importers, while others distribute the burden of proof to the customs administration. So, the legal problem that occurred in this study is regarding a different interpretation in applying the burden of proof. To solve that problem, it is necessary to research how the burden of proof applies in Tax Law through a comparative legal approach and research on how customs law regulates the burden of proof through a statute approach on WTO law and Indonesian customs law. The research results lead to one conclusion that the burden of proof can be shifted to companies or taxpayers if they cannot complete the evidence and documents required by tax or customs administration. However, the provision regarding the burden of proof for customs valuation is not clearly regulated in Indonesian Customs Law. Furthermore, the different interpretation in distributing the burden of proof among the judges is caused by the doctrine of freedom of proof based on tax court procedural law.